UNVEILING HALAL CERTIFICATION PROBLEMS IN MSMES: EVIDENCE FROM MALANG CITY - Farida, Maimunatul; Wicaksono, Ahmad Tibrizi Soni (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research aims to find out the reasons why MSMEs are reluctant to register for halal certification in Malang City. This research analysis uses a descriptive qualitative method of determining factors and indicators to improve the quality of research. The research results determined 4 codes i.e belief is halal, less information, not important and waste. The frequency of codes that appeared in this research was 128 codes derived from data collected in the form of interview transcripts. belief is halal is the code with the highest frequency followed by less information, not important and waste is the code that appears the least in the interview transcript.